2014
DOI: 10.1387/ijdb.130353ct
|View full text |Cite
|
Sign up to set email alerts
|

Two different vestigial like 4 genes are differentially expressed during Xenopus laevis development

Abstract: The vestigial gene (vg) was first characterized in Drosophila and several homologues were identified in vertebrates and called vestigial like 1-4 (vgll1-4). Vgll proteins interact with the transcription factors TEF-1 and MEF-2 through a conserved region called TONDU (TDU). Vgll4s are characterized by two tandem TDU domains which differentiate them from other members of the vestigial family. In Xenopus two genes were identified as vgll4. Our bioinformatic analysis demonstrated that these two genes are paralogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Tgi and VGLL4 contain two conserved Tondu domains responsible for the interaction with Sd and TEAD transcription factors, respectively ( Figure 1B) (GUO et al 2013;KOONTZ et al 2013). In addition, as reported previously (BARRIONUEVO et al 2014), we observed three conserved regions in Tgi: the N terminal region, and two short motifs between this region and the first Tondu domain ( Figure 1B). The first short conserved Tgi motif (PIDMS) bears strong resemblance to a consensus CtBP-interaction motif (PxDLS, where x is any amino acid) ( Figure 1C).…”
Section: Tgi Forms a Physical Complex With Pits And Ctbp Via Conservesupporting
confidence: 89%
“…Tgi and VGLL4 contain two conserved Tondu domains responsible for the interaction with Sd and TEAD transcription factors, respectively ( Figure 1B) (GUO et al 2013;KOONTZ et al 2013). In addition, as reported previously (BARRIONUEVO et al 2014), we observed three conserved regions in Tgi: the N terminal region, and two short motifs between this region and the first Tondu domain ( Figure 1B). The first short conserved Tgi motif (PIDMS) bears strong resemblance to a consensus CtBP-interaction motif (PxDLS, where x is any amino acid) ( Figure 1C).…”
Section: Tgi Forms a Physical Complex With Pits And Ctbp Via Conservesupporting
confidence: 89%
“…The VGLL4 TDU domains form bridges to interact with proteins such as TEAD1(26), IRF2BP2 [64] and Myocyte Enhancer Factor 2 (MEF2) [65]. Therefore, we injected Irf2bp2a , irf2bp2b , tead1a , tead3b , mef2ca and mef2cb mRNAs into zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
“…VGLL4 (MIM# 6186962) encodes vestigial-like family member 4 (Supplementary Table S6 and Figures 8-11). Studies in zebrafish (Xue et al, 2018), xenopus (Barrionuevo et al, 2014;Faucheux et al, 2010) and mice suggested that VGLL4 takes part in early embryonic development, including eye development. Interestingly, this gene is a part of the Hippo signaling pathway, which has also been implicated in myopia (Zhu et al, 2018).…”
Section: Bdnf (Mim# 113505) Encoding Brain-derived Neurotrophic Facto...mentioning
confidence: 99%